Functionalized silica nanoplatform as a bimodal contrast agent for MRI and optical imaging. Issue 39 (30th September 2021) - Garifo, Sarah; Stanicki, Dimitri; Boutry, Sébastien; Larbanoix, Lionel; Ternad, Indiana; Muller, Robert N.; Laurent, Sophie
Abstract : The preparation of an efficient bimodal single probe for magnetic resonance (MRI) and optical imaging (OI) is reported. Abstract : The preparation of an efficient bimodal single probe for magnetic resonance (MRI) and optical imaging (OI) is reported. Paramagnetic properties have been obtained by the non-covalent encapsulation of the clinically used Gd 3+ chelate ( i.e., Gd-HP-DO3A) within silica nanoparticles through a water-in-oil microemulsion process. To ensure colloidal stability, the surface of the particles was modified by means of treatment using PEG-silane, and further functionalized photochemically using a diazirine linker bearing carboxylic functions. Optical properties were obtained by the covalent grafting of a near-infrared emitting probe (NIR) on the resulting surface. The confinement of Gd complexes within the permeable matrix resulted in a significant increase in longitudinal relaxivities (>500% at 20 MHz) in comparison with the relaxivities of free chelate, while the post-functionalization process of PEG with fluorescent compounds appeared promising for the derivatization procedure. Several physico-chemical properties attested to the efficient surface modification and confirmed covalent grafting. Preliminary imaging experiments complete this study and confirm the potential of the presented system for preclinical imaging experiments.